Interventional radiology cases - Covey, Anne M.; Pua, Bradley; Aguado, Allison; Madoff, David C. (Cases in radiology., 2015)
In 104 cases featuring over 500, high-quality images, this book is a thorough and accessible review of the interventional procedures that radiology residents are expected to be familiar with upon completion of residency and general radiologists need to know for recertification examinations.